'Crisis' as a Relevant Lexeme in the Linguistic Consciousness of Ukrainian People - Gordiienko-Mytrofanova, Iia; Kobzieva, Iuliia; Bondar, Yuliia (East European Journal of Psycholinguistics, 2017)
The article presents the results of the psycholinguistic experiment whose aim was to reveal universal and specific features of the verbal behaviour of respondents when studying the stimulus word “crisis” as a relevant lexeme in the linguistic consciousness of Ukrainian people, as well as to single out various sememes that were actualised in the course of the experiment. The total sample comprised 297 respondents: 170 females and 127 males of different ages (“juvenility” – 17–21, “youth” – 22–35, “maturity” – 36–60, “old age” – 61 and above). The universal features of verbal behaviour displayed both by males and females are reflected in such lexemes as “money”, “age”, “economy”, “country”, “problem”, “poverty”, “unemployment”, “war”, “depression”, “misery”. The respondents of all age groups, both males and females, show negative evaluative and emotional attitude to the stimulus word in question. The specific features of the verbal behaviour of the respondents are reflected in the following lexemes: “bankrupt”, “panic”, “ruin”, “deadlock”, “chaos”, “Ukraine”. Among other things, both males and females associate crisis with the state of mental tension, anxiety, and fear, which manifests itself in such reactions as “depression”, “panic”, “negative”, “deadlock”, “bad”, etc. Individual features of verbal behaviour are reflected in the following negative emotional reactions: “pain”, “mess”, “mayhem”, “panic”, “fear”, “alarm”, “mix-up”, etc., with an obvious prevalence of female reactions. Associative reactions to the stimulus word "crisis" yield the following sememes: “lack of money”, “unemployment”, “problem”, “age”, “depression”, “opportunity”.ReferencesБашкова И. Слово «кризис» в русской речевой культуре //Journal of Siberian FederalUniversity. Humanities & Social Science, Supplement. 2009. C. 19–29.Bashkova, I. (2009). Slovo “krizis” v russkoy rechevoy culture [The word “crisis” inRussian speech culture]. Journal of Siberian Federal University. Humanities & SocialScience, Supplement, 19–29.Ворошилова М. «Алексей Леонидович! Нащупали дно?»: прецедентное имя вполитической карикатуре о мировом кризисе // Политическая лингвистика. 2010, №3(33). С. 61–63.Voroshilova, M. (2010). “Aleksey Leonidovich! Naschupali dno?”: pretsedentnoe imya vpoliticheskoy karikature o mirovom krizise [“Alexei Leonidovich! Have you found thebottom?”: A precedent name in the political caricature of the world crisis]. PoliticalLinguistics, 3(33), 61–63.Ворошилова М. Кризис – ключевое слово текущего периода: история изучения//Политическая лингвистика. 2012. № 3(41). С. 200–203.Voroshilova, M. (2012). Krizis – klyuchevoe slovo tekuschego perioda: istoriya izucheniya[Crisis – the key word of the current period: the history of study]. Political Linguistics,3(41), 200–203.Ворошилова М. Кризис сквозь смех: метафорический образ мирового кризиса врусской политической карикатуре. Политическая лингвистикa. 2010, №1(31). С. 90–94.Voroshilova, M. (2010). Krizis skvoz smeh: metaforicheskiy obraz mirovogo krizisa vrusskoy politicheskoy karikature [Crisis through laughter: a metaphorical image of the worldcrisis in the Russian political caricature]. Political Linguistics, 1(31), 90–94.Ворошилова М. У разбитого корыта: культурный прецедентный текст вполитической карикатуре о мировом кризисе // Политическая лингвистика. 2011,№1(35). С. 126–129.Voroshilova, M. (2011). U razbitogo koryita: kulturnyiy pretsedentnyiy tekst v politicheskoykarikature o mirovom krizise [At the broken trough: the cultural precedent text in thepolitical caricature about the world crisis]. Political Linguistics, 1(35), 126–129.Герасина Т., Погорелко А. Метафорическая модель экономического кризиса какпродукт национальной культуры// Политическая лингвистика. 2011, №4(38). С. 183–188.Gerasina, T., Pogorelko, A. (2011). Metaforicheskaya model ekonomicheskogo krizisa kakprodukt natsionalnoy kulturyi [The metaphorical model of the economic crisis as a productof national culture]. Political Linguistics, 4(38), 183–188.Немирова Н. Современный экономический кризис в зеркале прецедентности: мифыи реальность// Политическая лингвистика. 2010, №2(32). С. 132–138.Nemirova, N. (2010). Sovremennyiy ekonomicheskiy krizis v zerkale pretsedentnosti: mify irealnost [Modern economic crisis in the mirror of precedent: myths and reality]. PoliticalLinguistics, 2 (32), 132–138.Прокофьева Т. Концепт «кризис» в современном политическом дискурсе: Автореф.дис. … канд. фил. наук: 10.02.01. Санкт-Петербург, 2006.Prokofieva, T. (2006). Kontsept “Krizis” v Sovremennom Politicheskom Diskurse [TheConcept of “Crisis” in Contemporary Political Discourse]. Extended Abstract of Ph.D.dissertation. S.-Petersburg.Русский ассоциативный словарь. В 2 т. Под ред. Караулова Ю., Черкасовой Г.,Уфимцевой В., Сорокина Ю., Тарасова Е. М.: АСТ-Астрель, 2002.http://tesaurus.ru/dict/dict.phpRusskiy Assotsiativnyi Slovar [The Associative Thesaurus of the Russian Language]. In 2Volumes (2002). Karaulov, Yu., Cherkasova, G., Ufimtseva, V., Sorokin, Yu., Tarasov, E.(Eds.). Moscow: AST-Astrel. Retrieved from http://tesaurus.ru/dict/dict.phpСалатова Л. Отражение образов кризиса российскими СМИ // Политическаялингвистика. 2011, № 3(37). С. 162–166.Salatova, L. (2011). Otrazhenie obrazov krizisa rossiyskimi SMI [Reflecting images of thecrisis by Russian media]. Political Linguistics, 3(37), 162–166.Слатин А. Значение концепта «кризис» в российском политическом иэкономическом дискурсах// Современные научные исследования и инновации.2016, № 6. http://web.snauka.ru/issues/2016/06/68072.Slatin, A. (2016). Znachenie kontsepta “krizis” v rossiyskom politicheskom iekonomicheskom diskursah [The meaning of the concept of “crisis” in the Russian politicaland economic discourses]. Modern Scientific Research and Innovations, 6. Retrieved fromhttp://web.snauka.ru/issues/2016/06/68072.Цонева Л. Думата криза в медийния дискурс (българско-руски паралели). ВелкоТърново: ИВИС, 2012.Tsoneva, L. (2012). Dumata Kriza v Mediyniya Diskurs (Blgarsko-Ruski Paraleli) [TheWord Crisis in the Media Discourse (the Bulgarian-Russian Parallels)]. Velko Turnovo:IVIS.Шмелева Т. Кризис как ключевое слово текущего момента// Политическаялингвистика. 2009, №2(28). С. 63–67.Shmeleva, T. (2009). Krizis kak klyuchevoe slovo tekuschego momenta [Crisis as the keyword of the present moment]. Political Linguistics, 2(28), 63–67.